New Worlds in Astroparticle Physics : (World Scientific, 2003)
The Fourth International Workshop on New Worlds in Astroparticle Physics was the latest in the biennial series, held in Faro, Portugal. The program included both invited and contributed talks. Each of the sessions opened with a pedagogical overview of the current state of the respective field. The following topics were covered: cosmological parameters; neutrino physics and astrophysics; gravitational waves; beyond standard models: strings; cosmic rays: origin, propagation and interaction; matter under extreme conditions; supernovae and dark matter.